A retrospective, matched case-control study of recombinant LH versus hMG supplementation on FSH during controlled ovarian hyperstimulation in the GnRH-antagonist protocol - Chen, Ming-Jer; Yi, Yu-Chiao; Guu, Hwa-Fen; Chen, Ya-Fang; Kung, Hsiao-Fan; Chang, Jui-Chun; Chuan, Shih-Ting; Chen, Li-Yu (Frontiers in Endocrinology, 2022)
Background: The role of luteinizing hormone (LH) in controlled ovarian stimulation (COS) requires more evidence for its efficacy. Several studies compared recombinant LH (rLH) or human menopausal gonadotropin (HMG) in combination with recombinant follicle-stimulating hormone (rFSH) but lack the results with GnRH-antagonist protocol and in Asians. Methods: This is a retrospective, single-center study inspecting women receiving GnRH antagonist protocol and HMG+rFSH or rFSH+rLH regimen for over five days for COS in the in vitro fertilization (IVF)/ intracytoplasmic sperm injection (ICSI) cycle in Taiwan from 2013 to 2018. The outcomes of IVF/ICSI cycles were analyzed after propensity score matching between the two groups. A subgroup analysis was conducted in cycles in which women underwent their first embryo transfer (ET), including fresh and frozen ET (FET). Results: With a total of 503 cycles, the results revealed that the rFSH+rLH group performed better in terms of numbers of oocytes retrieved (HMG+rFSH vs. rFSH+rLH, 11.7 vs. 13.7, p=0.014), mature oocytes (8.7 vs. 10.9, p=0.001), and fertilized oocytes (8.3 vs. 9.8, p=0.022), while other outcomes were comparable. The analysis of first ET cycles also showed similar trends. Although the implantation rate (39% vs. 43%, p=0.37), pregnancy rate (52% vs. 53%, p=0.90), and live birth rate (39% vs. 45%, p=0.19) were not significantly different, the miscarriage rate was higher in the HMG+rFSH group than the rFSH+rLH group (26% vs. 15%, p<0.05) in first ET cycles. The cumulative pregnancy rate was significantly higher in the rFSH+rLH group (53% vs. 64%, p=0.02). No significant difference in rates of ovarian hyperstimulation syndrome (OHSS) was observed. Conclusion: The results support the hypothesis that the treatment of rLH+rFSH improves COS clinical outcomes in the IVF/ICSI cycle.